2021
DOI: 10.1177/00031348211046885
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Cost for Robotic vs “Non-Robotic” Transhiatal Esophagectomy

Abstract: Introduction This study was undertaken to analyze and compare the cost of robotic transhiatal esophagectomy (THE) to “non-robotic” THE (ie, “open” and laparoscopic). Methods With IRB approval, we prospectively followed 82 patients who underwent THE. We analyzed clinical outcomes and perioperative charges and costs associated with THE. To compare profitability, the robotic approach was analyzed against “non-robotic” approaches of THE using F-test, Mann-Whitney U test/Student’s t-test, and Fisher’s exact test. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…A propensity-score matched study from India found significantly higher costs for RAMIE in both matched and non-matched cohorts, but also lacked a detailed cost breakdown and had a small patient sample [ 23 ]. A US study reported similar costs for RAMIE and non-robotic esophagectomy (laparoscopic or open), but the non-robotic esophagectomy group was small [ 25 ]. Therefore, to the best of our knowledge, our analysis is the first to provide a detailed financial report on RAMIE and MIE for EC/GEJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A propensity-score matched study from India found significantly higher costs for RAMIE in both matched and non-matched cohorts, but also lacked a detailed cost breakdown and had a small patient sample [ 23 ]. A US study reported similar costs for RAMIE and non-robotic esophagectomy (laparoscopic or open), but the non-robotic esophagectomy group was small [ 25 ]. Therefore, to the best of our knowledge, our analysis is the first to provide a detailed financial report on RAMIE and MIE for EC/GEJ.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have reported higher financial expenses for robotic liver surgery compared to laparoscopic or open surgery [ 19 , 20 ], while others have shown equal or even lower costs [ 21 , 22 ]. Limited data is available regarding RAMIE: So far, reports from India [ 23 ], Germany [ 24 ] and the United States [ 25 ] have demonstrated higher financial expenses for RAMIE compared to MIE. Whether these cost differences can be offset by the potential benefits of RAMIE remains unclear [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The total cost of robotic distal pancreatectomy with or without splenectomy is like or less expensive than other operations of similar complexity. [10][11][12] Regardless of this technique's initial affordability, the financial implications of readmissions may hinder its viability in comparison to other techniques. There is a complete lack of literature addressing the financial implications of readmissions following robotic distal pancreatectomy and splenectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The robotic approach offers several potential benefits compared to traditional "open" and even minimally invasive laparoscopic approaches. These benefits may include improved visualization, enhanced dexterity, reduced blood loss, fewer incisions, and faster recovery times [2] . Studies have shown that, compared to non-robotic approaches, robotic THE has no apparent significant differences in charges, cost, or profitability [3] .…”
Section: Introductionmentioning
confidence: 99%